"A service we know was missing": bridging the gap between referral to admission for women with moderate-severe perinatal mental health disorders at an Australian psychiatric mother-baby unit. (December 2022) - Beaumont, Tara; Sved-Williams, Anne; Hill, Rebecca
Objectives: Service demand at Australian psychiatric mother-baby units is high. This project aimed to test a model of care providing step up/step down support to women with moderate-severe perinatal mental health disorders awaiting hospital admission. Method: A multi-disciplinary team was convened to provide pre-admission assessment and support to women waiting for admission, as well as post-discharge support as needed. Results: 108 referrals were managed between April – November 2021. With appropriate assessment and/or support in place, half of the women referred ( n = 54/108) were removed from the waitlist and avoided hospital admission. Service capacity indicators suggest a positive impact on referral numbers managed each week, as well as admissions per month. Conclusion: The tested model of care appears to have successfully improved service capacity; however longer term data is recommended to determine the sustainability of the trend towards increased capacity, and the acceptability of the model of care from a consumer perspective.